Prevalence and Predictors of Depression Among Pregnant Women Attending Antenatal Clinic (ANC) in a Tertiary Health Facility in a District of West Gujarat: A Cross-Sectional Study - Trivedi, Dr. Nidhi; M, YOGESH; Shah, Dr. Viral; Gandhi, Dr RohanKumar; Makwana , Dr. Naresh; agrawal, shaily; Parmar, Dr. Dipesh V. (International Journal of Innovative Research in Medical Science, 2023)
Background: Depression among pregnant women attending ANC is a prevalent and concerning issue with potential implications for maternal and fetal health outcomes. This study aims to contribute to the existing body of knowledge by examining the prevalence and predictors of depression among pregnant women in a district of West Gujarat. Methodology: The study was an Observational cross-sectional study conducted among pregnant women attending the ANC clinic of Tertiary Care Hospital, Western Gujarat during the period of Jan 2023 to May 2023. So, the Total sample of Pregnant Women was 266. Results: In the present study, the prevalence of depression was found to be 37%. Lack of partner or social support, history of abuse or domestic violence, previous history of psychiatric illness, poor marital relationship, stressful life events, a negative attitude towards the pregnancy, and lack of social support are some of the factors associated with antenatal depression. Women with a previous history of depression, Counterpart tobacco consumption status, and those who have experienced intimate partner violence are at higher risk of developing antenatal depression (P<0.05). Conclusion: Antenatal depression is a common mental health issue that can affect women during pregnancy. Early identification of pregnant women suffering from antenatal depression is important, and relevant support should be provided. Efforts are needed to strengthen or develop protocols for the early identification of pregnant women suffering from antenatal depression and provide relevant support